Marine and giant viruses as indicators of a marine microbial community in a riverine system. Issue 6 (9th August 2016) - Dann, Lisa M.; Rosales, Stephanie; McKerral, Jody; Paterson, James S.; Smith, Renee J.; Jeffries, Thomas C.; Oliver, Rod L.; Mitchell, James G.
Abstract: Viral communities are important for ecosystem function as they are involved in critical biogeochemical cycles and controlling host abundance. This study investigates riverine viral communities around a small rural town that influences local water inputs. Myoviridae, Siphoviridae, Phycodnaviridae, Mimiviridae, Herpesviridae, and Podoviridae were the most abundant families. Viral species upstream and downstream of the town were similar, with Synechoccocus phage, salinus, Prochlorococcus phage, Mimivirus A, and Human herpes 6A virus most abundant, contributing to 4.9–38.2% of average abundance within the metagenomic profiles, with Synechococcus and Prochlorococcus present in metagenomes as the expected hosts for the phage. Overall, the majority of abundant viral species were or were most similar to those of marine origin. At over 60 km to the river mouth, the presence of marine communities provides some support for the Baas‐Becking hypothesis " everything is everywhere, but, the environment selects ." We conclude marine microbial species may occur more frequently in freshwater systems than previously assumed, and hence may play important roles in some freshwater ecosystems within tens to a hundred kilometers from the sea. Abstract : This study investigates riverine viral communities around a small rural town that influences local water inputs. Overall, the majority of abundant viral species were or were most similar to those of marine origin. At over 60 km to the river mouth, the presence of marine communities suggests the microbial marine to freshwater transition region extends well beyond the salinity front, the river contains relict microbial communities, or that marine communities are intruding with the rising salinity in this regulated river. We conclude marine microbial species may occur more frequently in freshwater systems than previously assumed, and hence may play important roles in some freshwater ecosystems within tens to a hundred kilometers from the sea.